ENFORCEMENT OF DISCIPLINE OF STATE CIVIL SERVANTS (STUDY AT THE REGIONAL CIVIL SERVICE AGENCY OF SOUTH SULAWESI PROVINCE) - Amalia, Andi Radia Nur; Sakawati, Herlina; Nur, Andi Cudai; Aina, Asri Nur (Jurnal Aktor, 2025)
This study aims to find out how to enforce the discipline of the State Civil Apparatus in the BKD of South Sulawesi Province. This research uses a qualitative approach and produces descriptive data. Data collection was carried out by means of observation, interviews and documentation. The data was processed using interactive model analysis, namely data condensation, data presentation and conclusion drawn. The results of this study show that 1) Time discipline, employees in the Regional Civil Service Agency need to be improved because the frequency of employee attendance has not met the provisions in Government Regulations. 2) Regulatory discipline, employees in the Regional Civil Service Agency need to be improved, with some employees getting sanctioned or even fired from their jobs for lack of discipline. 3) Discipline of responsibility, employees in the Regional Civil Service Agency have not fully had a high awareness of responsibility in carrying out their duties according to applicable regulations, including in maintaining equipment, carrying out duties according to the code of ethics, and other rules that have an impact on work effectiveness and efficiency. Based on the findings of this study, recommendations to improve the discipline of the State Civil Apparatus with strict action on violations of ASN discipline in the Regional Civil Service Agency for a deterrent effect and increased productivity. The government is advised to foster civil servants in a clear and transparent manner, with career development, rewards for those who achieve, and strict sanctions for norm violators